Contribution Of Generation Z In Accelerating The Digitalization Of Sustainable Tourism In Benan Tourism Village, Lingga Regency - Rosie Oktavia Puspita Rini; Yudha Wardani; Astariadi Kurniawan (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
The Community Service Program (PkM) aims to optimize the contribution of Generation Z in accelerating the digitalization of sustainable tourism in Benan Tourism Village, Lingga Regency. As a leading marine destination based on Malay culture, Benan Village faces the challenge of the digital divide due to the limited technological literacy of senior tourism managers, at a time when the potential of local youth has not been channeled productively. This program uses a participatory approach (Participatory Appraisal) through project-based training methods and cross-sector mentoring that integrates two main partners, namely tourism village managers (Pokdarwis) and local school institutions. The series of activities includes needs analysis, creative content creation workshops, social media management, and digital governance assistance. The results of PkM show a significant increase in students' literacy and digital skills as a representation of Generation Z. The resulting concrete contribution is the formation of a collaborative digital working group between schools and Pokdarwis who act as local content creators. This group independently succeeded in strengthening the 3A tourism pillar (Attractions, Amenities, Accessibility) in cyberspace through a visual narrative with the theme of eco-tourism. The sustainability of this program has succeeded in building a social media tourism ecosystem that effectively attracts niche travelers. In conclusion, the synergy of independence between schools and tourism village managers has succeeded in transforming the role of Generation Z into agents of digital change, as well as long-term investment to maintain the competitiveness and resilience of the sustainable creative economy of Benan Tourism Village.